TELISIK PERLAKUAN TEORI ENTITAS USAHA MIKRO, KECIL DAN MENENGAH - Sari, Dian Purnama (Jurnal Akuntansi Multiparadigma, 2013)
Abstract: Study of Entity Theory Treatment on Micro, Small and Medium Enterprises (SMEs). Various challenges and obstacles still occur in SMEs development in Indonesia. One of them is the behavior of SMEs owners who often do not separate personal finance and business capital. Habit of paying for any personal needs is one form of the use of enterprise wealth for personal use. This social reality of SMEs shows the incomprehension of the Economic Entity Concept, the tendency to use the enterprise wealth for personal reason, and business profit/income is treated as âownerâs walletâ. Internalization process can be carried out by âtransplantationâ of the economic entity concept to eliminate the culture of âsami mawonâ exhibited by many actors of SMEs. Abstrak: Telisik Perlakuan Teori Entitas dalam Usaha Mikro, Kecil dan Menengah (UMKM). Beragam tantangan dan hambatan masih memayungi pengembangan UMKM di Indonesia. Salah satunya adalah perilaku pemilik UMKM yang seringkali tidak memisahkan modal bisnis keuangan pribadi dan perusahaan. Kebiasaan pembayaran pelbagai kebutuhan pribadi adalah salah satu bentuk penggunaan sumber daya usaha untuk kepentingan pribadi. Realitas sosial UMKM semacam ini menunjukkan penerapan konsep entitas ekonomi yang tidak komprehensif, kecenderungan penggunaan sumber dayaÂ  untukÂ  pribadi dan laba/pendapatan usaha bisnis sebagai âkantong ribadi pemilikâ. Proses internalisasi melalui âtransplantasiâ konsep entitas ekonomi dapat diikhtiarkan dalam memberantas budaya âsami mawonâ yang dilakoni banyak aktor UMKM.